Raman spectroscopy analysis of the skin of patients with melasma before standard treatment with topical corticosteroids, retinoic acid, and hydroquinone mixture. Issue 2 (14th July 2015) - Moncada, B.; Castillo‐Martínez, C.; Arenas, E.; León‐Bejarano, F.; Ramírez‐Elías, M. G.; González, F. J.
Abstract : Background: Melasma is an abnormal acquired hyperpigmentation of the face of unknown origin, it is considered a single disease and very little has been found regarding its pathogenesis. It is usually assumed that melasma is due to excessive melanin production, but previous work using Raman spectroscopy showed degraded molecules of melanin in some melasma subjects, which may help to explain the success or failure of the standard therapy. Methods: We perform Raman spectroscopy measurements on in vivo skin from melasma patients before treatment to identify the molecular structure of melanin within every melasma lesion. The Raman spectra were grouped according to the treatment response from patient, and the Raman spectra were analyzed. Results: Raman spectroscopy measurements showed a different molecular structure of the patients who did not respond to treatment, those patients shows atypical Raman skin spectrum with peaks associated with melanin not well defined, which is consistent with molecular degradation and protein breakdown. Conclusion: Our results are consistent with our previous work in the sense that melasma patients who do not respond to treatment have an abnormal melanin. We believe it will eventually help to decide the treatment of melasma in clinical dermatology.